The Situation of Non-Heteronormative Person in Administrative Law - Puczko, Aleksandra (Acta Universitatis Lodziensis. Folia Iuridica, 2023)
The aim of this paper is to discuss the key issues related to legal situation of nonheteronormative person in administrative law. As it can be seen from the number of the judgements issued by the courts, the practical side of the problem is of significance. For this reason, it is worth to make an attempt to analyze the grounds of connection between sexual orientation and identity and dignity and by that the failure of the protection system, that it does not cover in a proper way the non-heteronormative person. The paper is dedicated to show the weak points of the legal system that lead to the breaching the dignity and by that the basic human rights, connected with sexual freedom. The analysis is conducted from the point of view of making and implementing the law.